Resistencia bacteriana a los antibióticos en apendicitis aguda - Solórzano Llerena, Jonathan Omar (2019)
Since their appearance, antibiotics have been and are an important weapon for the treatment of many infectious diseases, some of which caused high mortality, and their use made it possible to significantly and notably reduce the morbidity and mortality of some of these diseases. Currently, in acute appendicitis, the prophylactic administration of antimicrobials is considered by many surgeons as important and indispensable as the application of the antisepsis rules during the intervention, with particular attention to the most effective agent. Bacterial resistance is a growing phenomenon characterized by a partial or total refractoriness of the microorganisms to the effect of the antibiotic generated mainly by the indiscriminate and irrational use of these and not only by the evolutionary pressure that is exerted in the therapeutic use. At Víctor Lazarte Echegaray Hospital in Trujillo, the antibiotic prophylaxis in acute appendicitis is performed once the clinical diagnosis of acute appendicitis is had, it is used intravenously, Ciprofloxacin 400mg every 12h + Metronidazole 500mg every 8h until discharge . With the present research we seek to know the microbiological and resistance profile of the microorganisms present in patients diagnosed with acute appendicitis in the Surgery Service of Víctor Lazarte Echegaray Hospital to develop an updated effective antibiotic protocol.